BACKDRAFT . 2 - Anderson, Joe; Baldwin, William; De Laurentiis, Raffaella; Lopez-Gallego, Gonzalo; Sutherland, Donald; Widen, Gregory (California : UNIVERSAL 1440 ENTERTAINMENT, 2019)
The sequel to the 1991 hit, follows an investigator with the Chicago F.D., who has to track down an arms dealer who use deadly fires as a distraction
Widescreen 2.00:1
Joe Anderson, William Baldwin, and Donald Sutherland
Keywords: Motion pictures; Action and adventure films; Crime films